An unprecedented benzannulation of oxindoles with enalcarbenoids: a regioselective approach to functionalized carbazoles. Issue 34 (18th March 2016) - Rathore, Kuldeep Singh; Lad, Bapurao Sudam; Chennamsetti, Haribabu; Katukojvala, Sreenivas
Abstract : An unusual rhodium-catalyzed tandem reaction of oxindoles with diazoenals involving the cleavage of sp 2 C–O and sp 2 C–C bonds resulted in the formation of 1-hydroxy-2-acylcarbazoles. Abstract : A novel Rh(ii )/Brønsted acid catalyzed tandem benzannulation of oxindoles with enaldiazo carbonyls led to the formation of valuable 1-hydroxy-2-acylcarbazoles. This reaction is proposed to involve a formal insertion of a rhodium enalcarbenoid into an oxindole sp 2 C–O bond, an oxa-Michael addition, Friedel–Crafts reaction and a semipinacol type 1, 2-carbonyl migration.